9. Navigated transcranial magnetic stimulation (nTMS) for preoperative mapping in motor areas tumor surgery: Comparison with functional magnetic resonance imaging (fMRI) and intraoperative direct cortical stimulation. Issue 12 (December 2016) - Lettieri, C.; Budai, R.; Devigili, G.; Muggiolu, F.; Rinaldo, S.; Canesin, R.; Valiante, G.; Ius, T.; Skrap, M.; Eleopra, R.
Abstract : Navigated transcranial magnetic stimulation (nTMS) is a novel technology in the field of neurosurgery for noninvasive delineation of cortical functional topography. Recent studies show that it can detect eloquent cortical areas directly, comparable to intraoperative direct cortical stimulation (DCS). The aim of this study was to evaluate the nTMS in comparison with functional magnetic resonance imaging (fMRI) in the setting of brain tumors involving motor areas. Thirteen consecutive patients affected by frontal lobe brain tumors were enrolled in the study. All patients received an fMRI and nTMS examination preoperatively. Consistency of preoperative mapping with intraoperative DCS was assessed off-line by means of the neuronavigation system: as result, nTMS produced statistically significant higher accuracy scores of the motor area localization than fMRI. Moreover, nTMS has fewer restrictions for preoperative functional mapping than fMRI and requires only a limited level of compliance: so it represents an useful and reliable technique during preoperative planning for surgical decision making in the clinical setting.